Jogando o jogo dos tronos : ruptura e inovação na obra de George R. R. Martin - Correa, Murilo Filgueiras (2015)
The objective of this study is to ponder on the processes of reading, reception and adaptation of the two first literary works of the series A Song of Ice and Fire, A Game of Thrones (2010) and A Clash of Kings (2011) by George RR Martin, as well as the first and second seasons of the television series produced by HBO, Game of Thrones, broadcasted between 2011 and 2012. Therefore it was necessary to analyze its construction and characterization, especially in representations of archetypal figures as hero and villain, and also the public's reaction on witnessing deaths, in a way, of some unexpected characters. Martin builds his loaded characterizations already canonized in certain narrative styles, which therefore generate expectations, in general, very specific about reading or watching a tv show. These expectations generates a huge debate about what are the real issues that the works actually expose are, raises questions about ethical and moral concepts, and ultimately destabilizes the public's horizons of expectations, forcing them to restructure it by filling the newly created voids through questioning and deconstructing receptional and semantic instances long established. The study participants were selected in virtual social networks and participated voluntarily in the study, sharing their reactions and discussing the controversies raised by the works. In order to analyze the interviews, as well as support the ponders on George RR Martin's, the theoretical framework of the study took advantage of views on the Aesthetics of Reception proposed by Hans Robert Jauss (1994), the concepts of reading and the reader by Wolfgang Iser (1996, 1999), technical specifications and their semantic projections pointed out by Umberto Eco (1994) and Yves Reuter (2011); as well as the concepts of adaptation between medias brought by Linda Hutcheon (2011), and about the culture of convergence through Henry Jenkins's texts (2009). The results indicated that the reception of the works by the group of volunteers was composed by a mix of surprises, disappointments, disintegration and re-establishment of conventions and horizons of expectation. Participants effectively demonstrated the incorporation of new ways to react and interact with a story, provided by both literary and television works, and how these new aesthetic effects are likely to influence their next readings. From ahead the present study, the possibility of review and further discussions about archetypal representations of hero and villain, as well as their trajectories within the dramatic narrative shows plausible for the establishment of new issues and future considerations, since one of the greatest Martin's trump among its readers and spectators is precisely the surprises, said, unpleasant while adverse to long-established narrative conventions.